Factors Associated With Clopidogrel Adherence in Community-Dwelling Patients. Issue 5 (September 2016) - Momary, Kathryn M.; Kimble, Laura P.
Abstract : Objective: The purpose of this study was to characterize predictors of adherence to clopidogrel therapy focusing on patients' perceptions of clopidogrel and nuisance bleeding. Methods: This was a cross-sectional study of community-dwelling cardiovascular patients with a self-reported prescription for clopidogrel. Self-report questionnaires assessed depressive symptoms, social support, nuisance bleeding, perceptions of clopidogrel, and adherence to therapy. Low, moderate, and high adherence groups based on the Morisky Medication Adherence Scale were compared and hierarchical multiple linear regression analysis was used to predict adherence. Results: A total of 102 subjects were enrolled, and 55%, 28%, and 16% were classified as having low, moderate, and high adherence, respectively. Greater perceptions of clopidogrel necessity, lower perception of clopidogrel concern, and increased severity of nuisance bleeding were predictors of better adherence. Conclusions: Data from this cross-sectional study suggest that concerns about clopidogrel and feelings about its necessity play an important role in clopidogrel adherence.